Mechanism of heterogeneous flow—solid substrate interaction on the formation of coatings of different thicknesses using different types of spray accelerators - Borisov Sergey; Gloukhovskaya Julia; Dobrovolskiy Sergey; Myakochin Alexander; Podporin Igor (MATEC Web of Conferences, 2022)
Physical processes of the inleakage of a supersonic heterogeneous flow of air-powder mixture to a solid substrate, tested on the experimental setup designed for applying protective coatings by a cold spray method, are considered. The interaction of a particle with a flat plane and cylindrical solid substrates, the multilayer coatings and the application of coatings using spray accelerators of different configurations are considered. A mathematical model is demonstrated based on the equation of energy balance in the impact area intended to estimate the interaction between a particle and a solid substrate during impact, as well as examples of results calculated using this model. Methods for calculation of the thickness of the coating applied to flat plane and cylindrical substrates are described. The features of one-step and multi-step coating applications with and without additional exposures are described. As an example, the results of testing the coating for porosity are given. A list of factors and additional exposures affecting the strength of the coating is given.